Cyclic Voltammetry of Cobalt Chloride with L- Carrageenan (LK) Using Glassy Carbon Electrode - E. Gomaa; A. Negm; R. Abou Qurn (Iranian Journal of Chemical Engineering)
The redox behavior cobalt chloride was studied voltammetrically in presence and absence of L- Carrageenan (LK) natural polymer using glassy carbon electrodes in 0.1 M KCl supporting electrode. Scan rates are studied for the redox behaviors for CoCl2 alone or in presence of L- Carrageenan (LK) natural polymer. Stability constants for the interaction of cobalt ions with L - Carageenan (LK) natural polymer are evaluated. All mechanisms are discussed.The redox behavior cobalt chloride was studied voltammetrically in presence and absence of L- Carrageenan (LK) natural polymer using glassy carbon electrodes in 0.1 M KCl supporting electrode. The interaction of CoCl2 with L-Carrageenan (LK) has been studied using cyclic voltammetry technique in the potential range (+1.5 to -1.0) V at different scan rates in water at 292.15 oK using KCl (0.1M) as supporting medium and glassy carbon as a working electrode. The study is valuable for evaluating the thermodynamic properties [3-18]. The cobalt ions used show two oxidation peak at 0.02 and 0.06 V and two reduction peaks at 0 and -0.7 V These two peaks corresponding to the oxidation of cobalt zero valent to monovalent and then the oxidation of cobalt monovalent to divalent cobalt Scan rates are studied for the redox behaviors for CoCl2 alone or in presence of L- Carrageenan (LK) natural polymer. Stability constants for the interaction of cobalt ions with L - Carageenan (LK) natural polymer are evaluated. All mechanisms are discussed.